Dall’Iliade. Etica senza alterità - Meattini, Valerio (Bollettino Filosofico, 2019)
The convergences of Giacomo Leopardi, Simone Weil and Rachel Bespaloff in reading the Iliad are impressive. This holds not only as regards the meaning and value of the poem but also concerning the almost equal interpretation of fundamental passages and the use of expressions that sometimes coincide literally. These convergences open up to a both original and originary ethical dimension, a dimension that allows us to think about ourselves in a condition of radical equality. We are thus dealing with an ethics that precedes morality, law, politics and cultures, an ethics originating from the recognition of the condition of dependence: yesterday from the fatum, today from our biological constitution and the complex of social relations. Such an ethics reaches its goal in the compassion as well as in the awareness that the liberation process must take on this ethical perspective. Keywords: Homer, Ethics, Cosmos, Fatum, Violence